Exploring the genetic resources of yam in the Democratic Republic of Congo: implications for breeding - Adejumobi, I.; Adewumi, A.S.; Ouattara, F.; Olatunde, E.; Adheka, J.; Onautshu, D.; Kayondo, S.I.; Alaba, O.; Mushoriwa, H.; Agre, P.A. (Frontiers Media, 2024)
Introduction: Landrace accession of yam species in the Democratic Republic of Congo (DRC) represents a valuable genetic resource for yam breeding programs. These accessions possess traits such as stress resilience and desirable food quality attributes that can be introduced into modern yam varieties. By analyzing the genetic diversity, identifying quantitative trait loci (QTLs) linked to key traits, and the genetic merits of these landraces, we can identify promising genetic markers for breeding programs aimed at improving yam production in DRC.